Cognitive and behavioral associated changes in manifest Huntington disease: A retrospective cross‐sectional study. Issue 7 (10th June 2021) - Migliore, Simone; D'Aurizio, Giulia; Maffi, Sabrina; Ceccarelli, Consuelo; Ristori, Giovanni; Romano, Silvia; Castaldo, Anna; Mariotti, Caterina; Curcio, Giuseppe; Squitieri, Ferdinando
Abstract: Introduction: Behavioral and cognitive changes can be observed across all Huntington disease (HD) stages. Our multicenter and retrospective study investigated the association between cognitive and behavioral scale scores in manifest HD, at three different yearly timepoints. Methods: We analyzed cognitive and behavioral domains by the Unified Huntington's Disease Rating Scale (UHDRS) and by the Problem Behaviors Assessment Short Form (PBA‐s), at three different yearly times of life (t0 or baseline, t1 after one year, t2 after two years), in 97 patients with manifest HD (mean age 48.62 ± 13.1), from three ENROLL‐HD Centers. In order to test the disease progression, we also examined patients' motor and functional changes by the UHDRS, overtime. Results: The severity of apathy and of perseveration/obsession was associated with the severity of the cognitive decline ( p  < .0001), regardless of the yearly timepoint. The score of irritability significantly and positively correlated with perseveration errors in the verbal fluency test at t0 ( r  = .34; p  = .001), while the psychosis significantly and negatively correlated with the information processing speed at t0 ( r  = −.21; p  = .038) and significantly and positively correlated with perseveration errors in the verbal fluency test at t1 ( r  = .35; p  < .0001). The disease progression was confirmed by the significant worsening of the UHDRS‐Total Motor Score (TMS) and of the UHDRS‐Total Functional Capacity (TFC) scale score after two‐year follow‐up ( p  < .0001). Conclusion: Although the progression of abnormal behavioral manifestations cannot be predicted in HD, the severity of apathy and perseveration/obsessions are significantly associated with the severity of the cognitive function impairment, thus contributing, together, to the disease development and to patients' loss of independence, in addition to the neurological manifestations. This cognitive‐behavior pattern determines a common underlying deficit depending on a dysexecutive syndrome. Abstract : Severity of apathy and perseveration/obsessions are significantly associated with the severity of the executive function impairment. This association may represent an additional key factor contributing to the severity of Huntington disease course. This cognitive‐behavior pattern determines a common underlying deficit attributable to a dysexecutive syndrome.